Does Insurance Market Activity Promote Economic Growth? A Cross-Country Study for Industrialized and Developing Countries - Arena, Marco (World Bank, Washington, DC, 2012)
Insurance market activity, both as a financial intermediary and a provider of risk transfer and indemnification, may contribute to economic growth by allowing different risks to be managed more efficiently and by mobilizing domestic savings. During the past decade, there has been faster growth in insurance market activity, particularly in emerging markets given the process of liberalization and financial integration, which raises questions about its impact on economic growth. The author tests whether there is a causal relationship between insurance market activity (life and nonlife insurance) and economic growth. Using the generalized method of moments for dynamic models of panel data for 56 countries and for the 1976-2004 period, he finds robust evidence of a causal relationship between insurance market activity and economic growth. Both life and nonlife insurance have a positive and significant causal effect on economic growth. High-income countries drive the results in the case of life insurance. On the other hand, both high-income and developing countries drive the results in the case of nonlife insurance.